RNA-sequencing identified miR-3681 as a negative regulator in the proliferation and migration of cervical cancer cells via the posttranscriptional suppression of HGFR. Issue 39 (18th July 2019) - Shi, Fan; Zhang, Yingbing; Wang, Juan; Su, Jin; Liu, Zi; Wang, Tao
Abstract : In this study, RNA-sequencing was used to investigate the differentially expressed miRNAs between cervical cancer tissues and matched adjacent non-tumor tissues. Abstract : In this study, RNA-sequencing was used to investigate the differentially expressed miRNAs between cervical cancer tissues and matched adjacent non-tumor tissues. Five miRNAs were sharply downregulated in the cancer tissue, including miR-199a, miR-22, miR-615, miR-3681-3p (miR-3681), and miR-1193. Among them, miR-3681 was uncharacterized. The results from qPCR analysis showed that miR-3681 expression was decreased in patients with cervical cancer compared with the control, and decreased in the human cervical cancer cell lines SiHa, HeLa, C4-1, C-33A and Caski, compared with the normal human cervical epithelial cell line HCerEpic. Then, different concentrations of miR-3681 mimic and miR-3681 inhibitor were respectively transfected into the human cervical cancer cell line C-33A, and the expression of miR-3681, cell proliferation, cell apoptosis and cell migration were measured after 48 h. The results showed that the miR-3681 mimic increased the miR-3681 level, suppressed cell proliferation and migration, and induced cell apoptosis in a dose-dependent manner. In contrast, the miR-3681 inhibitor decreased the miR-3681 level, promoted cell proliferation and migration, and inhibited cell apoptosis in a dose-dependent manner. Moreover, bioinformatics analysis showed that there was a miR-3681 binding site in the mRNA 3′UTR of HGFR, which was robustly upregulated in cervical cancer cell lines compared with HCerEpic cells. In addition, luciferase activity analysis demonstrated that miR-3681 could directly target HGFR, which promoted the proliferation and migration of C-33A cells via activation of the PI3K/Akt pathway in a dose-dependent manner. Furthermore, our results showed that knockdown of HGFR could antagonize the promotion of anti-miR-3681 on the activation of the PI3K/Akt pathway and cell proliferation and migration. In conclusion, MiR-3681 was identified as a negative regulator in the proliferation and migration of cervical cancer cells. This function is associated with the posttranscriptional suppression of HGFR and the deactivation of the PI3K/Akt pathway.